Characterization of the sedimentary record of the AD1755 tsunami in the Martinhal Holocene succession (Algarve, Portugal) Caracterização do registo sedimentar do tsunami de 1755, na sucessão holocénica do Martinhal (Algarve, Portugal) - Cunha, Pedro (2016)
This study addresses the Holocene sedimentary succession at Martinhal coastal lowland (Algarve), a site recording the AD1755 Lisbon tsunami. Data on twenty-four short cores and sixteen trenches, retrieved from both the literature and new field work were combined to improve the stratigraphic resolution and lateral correlation of sedimentary units accumulated in this lowland. Four fining-upward depositional sequences (S1 to S4) were identified, showing spatial variation with maximum thickness - S1: 0-3 m; S2: 1.0-2.4 m; S3: 0.2-1.0 m; S4: 0.3-2.3 m. Sequences S1, S2 and S3 consist of medium to coarse yellow sands with levels rich in bioclasts that give place upsequence to brown organic silt and clay. Sequences S1 to S3 testify to the progressive infilling of a small estuary, coeval with the progressive development and changes in efficiency of a sandy barrier. The uppermost sequence (S4) is clearly different and also shows contrast in facies at seaward and landward locations. S4 comprises: 1) seaward (ESE), a basal subunit with boulders to pebbly gravels and coarse to medium well sorted sands, interpreted as deposited by the AD1755 tsunami, covered by an upper subunit comprising an alternation of well sorted white sands and brown silts, interpreted as aeolian/washover and flood deposits; 2) upstream (WNW), alternating layers of poorly sorted very coarse to medium sands and brown silts represent flood plain accretion and channel infill within the lowland. Quartz OSL dating was done by measuring small aliquots in samples from the AD1755 event-layer and large aliquots in samples from other deposits. The coarser and more basal sediment of the AD1755 sediment yielded overestimated OSL ages due to partial bleaching; at the top, and in finer sediment, and also in the more landward locations, OSL ages are closer to the true age of this event. At this location, routine Quartz OSL dating using large aliquots can give useful data on the burial ages for a variety of sediments, provided that the burial time exceeds ca. 1 ky. In contrast, recent abrupt-event sediments should be dated by measuring small aliquots or single grains to get a better control on partial bleaching effects on OSL results.